Burkina Faso PNDSA II Impact Analysis Baseline Survey, 2002-2003 - International Food Policy Research Institute (International Food Policy Research Institute, 2006)
This dataset is the baseline survey for the impact evaluation of the World Bank- funded program: PNDSA II (Programme National de Services Agricoles) in Burkina Faso. The objective of this program was to strengthen the Rural Producers Organizations (POs) capacities to provide services for their members. The program also created PO councils at the district level "Départements" in Burkina Faso, through which the organizations can exchange information on their experiences. The sampling design included several independent strata meant to reflect different agro-ecological areas in the North, the Central North, the West, the South, and the Southeast. Within each district, 14 villages were randomly selected. When the number of villages in the district was less than 14, all villages were included in the sample and additional villages were eventually selected in larger districts. Four series of questionnaires were used: village-level; household-level; PO-level; and specific PO activities. Topics covered are information at the village level; basic information on all households in the community, including their participation in the different POs in the village; information on all POs in the village (with a limit of five), and on collective field, cotton, trade, and horticulture when such activities were undertaken by the POs. A related survey is Senegal PSAOP Impact Analysis Baseline Survey, 2002-2003, which used similar questionnaires in Senegal.